AC Albright barley - Wolfe, R. I.; Dofing, S. M.; Davidson, J. G. N.; Clarke, P. J. (Canadian Journal of Plant Science, 1995)
AC Albright (Hordeum vulgare L.) is an early maturing, six-row feed barley cultivar. It was selected from the cultivar Otal at the Northern Agriculture Research Centre, Agriculture and Agri-Food Canada, Beaverlodge, Alberta Canada. It has demonstrated adaptation to north-central and western Alberta and the Peace River region of British Columbia. Key words:Hordeum vulgare, barley, early maturity, cultivar description